Pore-Scale Study of the Non-Linear Mixing of Fluids with Viscous Fingering in Anisotropic Porous Media (Communications in Computational Physics, 2018)
Mixing processes of miscible viscous fluids in anisotropic porous media arestudied through a lattice Boltzmann method in this paper. The results show that fluidmixing can be enhanced by the disorder and interfaces induced by viscous fingers.Meanwhile, the permeability anisotropy affects the developments of viscous fingersand the subsequent mixing behaviors significantly. Specifically, as the streamwise (longitudinal)permeability is larger than the spanwise (transverse) one, the mixing processis faster and stronger than that in the contrary case. Furthermore, the anisotropycan lead to different behaviors of the dissipation rates in streamwise and spanwisedirections. Generally, the dissipation rate is dominated by the transverse concentrationgradients when the longitudinal permeability is higher than the transverse one;on the contrary, as the transverse permeability is higher than the longitudinal one, thecontributions to the dissipation rate from longitudinal and transverse concentrationgradients are both significant.